Os desafíos do Ensino de Geografía na relação campo-cidade: provocações a partir do debate da Educação do Campo - Batista, Ana Lídia Santana (2016)
This research was mainly aimed to investigate the role of geography teaching to the understanding of city-country relationships, work with students Elementary School II in the municipality of Irará. This discussion was based on the analysis of the reality of the Maria Bacelar School – EMMB, located in Trinity Farm – Irará, BA. The research was analysis of the background, the Countryside Education debates, and discussions started from the 90s of the twentieth century, led by rural social movements articulate that with other individuals and institutions, and unleashed the Movement towards a Countryside Education. This debate defends an educational proposal that overcomes the emptying of socio-political content in order to contribute to the working class, especially the countryside understand the socio-spatial reality in its entirety and fight for the transformation of the conditions that prevent them from living with dignity. To conduct this research I opted for a qualitative approach, using tools such as bibliographic and documentary research, interviews with geography woman teachers, questionnaires to students of elementary school II as well as their parents. In this study, countryside-city relationship was approached as main-theme that articulated all the work, understood as a category that structures the geographical thought and by extension the geography teacher's work, since this relationship permeates implicitly or explicitly all the themes of the course . Through this study, I noted that among other factors, due to the absence of public policy training for teachers who work in schools in the countryside in Irará the lack of a curriculum that considers the specificities of subjects in the countryside, the teacher's work of Geography in EMMB tends to contribute to a dichotomous and hierarchical view of the countryside and the city, strengthening a school project that denies farmers values for the benefit of the urban way of life. Such perspective of work, contributes to some extent to reinforce the inferiority of view that students of the countryside have built over the rural area and consequently about themselves, weakening the peasants' struggle for land, while social struggle in defense of life reproduction with dignity. On the other hand, these woman teachers are aware that this proposal does not meet the specific needs of students from the countryside teachers are aware that this proposal does not meet the specific needs of students from the countryside, showing open the implementation of a pedagogical proposal against hegemonic. It is in this contradictory field that enters the Countryside Education debate as a possibility to think a school education that contributes to the emancipation of these subjects.